2012
DOI: 10.22605/rrh2201
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exchange throughout the dementia care journey by Canadian rural community-based health care practitioners, persons with dementia, and their care partners: an interpretive descriptive study

Abstract: Introduction: Accessing, assessing, exchanging, and applying dementia care information can be challenging in rural communities for healthcare practitioners (HCPs), persons with dementia (PWD), and their care partners. The overall purpose of this research was to enable HCPs, care partners, and PWD to use dementia care information more effectively by examining their information needs, how these change over time, and how they access, assess, and apply the knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
1
25
1
1
Order By: Relevance
“…This not only aligns with Canadian recommendations 13,14 but also with the evidence that patients generally value continuity of care 23 and might prefer being diagnosed and treated by their family physicians. [24][25][26] The Quebec Alzheimer Plan employed a multifaceted strategy to address primary dementia care, 27 dementia care. This comprehensive approach was successful in improving dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…This not only aligns with Canadian recommendations 13,14 but also with the evidence that patients generally value continuity of care 23 and might prefer being diagnosed and treated by their family physicians. [24][25][26] The Quebec Alzheimer Plan employed a multifaceted strategy to address primary dementia care, 27 dementia care. This comprehensive approach was successful in improving dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…Les réponses des cliniciens de soins primaires à nos questionnaires ont démontré que les médecins de famille, les infirmières et les autres professionnels de la santé qui avaient participé à la mise en oeuvre du Plan Alzheimer du Québec avaient des CAP bonnes ou positives 13,14 , mais aussi avec les données probantes voulant que les patients valorisent généralement la continuité des soins 23 , et pourraient préférer recevoir le diagnostic et leurs traitements de leur médecin de famille [24][25][26] . Le Plan Alzheimer du Québec utilisait une stratégie à multiples facettes pour aborder les soins primaires de la démence 27 , notamment : des ressources cliniques, financières et en gestion du changement; le recours à des équipes multidisciplinaires; de même que de la formation et de l'encadrement en soins pour la démence.…”
Section: Discussionunclassified
“…Five studies (17%) discussed current KT and patient engagement initiatives designed to support cognitively impaired patients and their circle of care in ACP (Arcand et al, 2013; Bayly, Blake, Peacock, Morgan, & Forbes, 2018; Forbes et al, 2012; van der Steen et al, 2012; Waxman, Russell, Iu, & Mulsant, 2018). Two studies examined the usefulness, quality, and acceptability of information booklets on dementia and end-of-life care (Arcand et al, 2013; van der Steen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a study by Forbes et al (2012) explored the information needs of multiple Southwestern Ontario stakeholders in dementia care as well as how these needs changed over time and how the aforementioned parties accessed, assessed, and applied dementia care knowledge. In this study, six stages to the dementia care journey were identified: “(1) recognizing the symptoms, (2) receiving a diagnosis, (3) loss of independence, (4) initiating and using home care and respite services, (5) LTC placement, and (6) decisions related to end-of-life care.” Rural care partners communicated that each stage required unique knowledge and that persons living with dementia rarely recognized a personal need for dementia care information.…”
Section: Resultsmentioning
confidence: 99%